Perancangan Sistem Informasi Presensi Peserta Praktikum Di Fakultas Teknik Universitas Sebelas Maret Surakarta - suparmo Suparmo (Politeknik Harapan Bangsa Surakarta, 2023)
Sebelas Maret University Surakarta (UNS) applies an assessment system for student attendance in attending practicum lessons by 75%. In many cases, students who are not present can entrust attendance signatures to their friends to fill out the attendance list that is circulated in the practicum class. This is one of the factors that makes the assessment of student knowledge and competence doubtful. Another problem that exists in the presence section is the absence of a computerized attendance system equipped with automated attendance data calculations. The current attendance system only utilizes the Microsoft Excel application, whose report generation still uses manual input. This can allow for errors in inputting student attendance data. Based on the description of the background, it can be formulated the problem to be solved in this research is